When is the right time for Fontan conversion? The role of cardiopulmonary exercise test. (1st October 2016) - Egbe, Alexander C.; Connolly, Heidi M.; Dearani, Joseph A.; Bonnichsen, Crystal R.; Niaz, Talha; Allison, Thomas G.; Johnson, Jonathan N.; Poterucha, Joseph T.; Said, Sameh M.; Ammash, Naser M.
Abstract: Background: To determine if Fontan conversion (FC) resulted in improvement in exercise capacity (EC), and to determine the role of cardiopulmonary exercise test (CPET) in risk stratification of patients undergoing FC. Methods: A retrospective review of patients who underwent CPET prior to FC at Mayo Clinic from 1994 to 2014. The patients who also underwent post-operative CPET were selected for the analysis of improvement in EC defined as 10% increase in baseline peak oxygen consumption (VO2 ). Results: 75 patients CPET prior to FC; mean age 24 ± 6 years; 44 males (59%); and 51 (68%) were in NYHA III/IV prior to FC. Pre-operative peak VO2 was 15.5 ± 3.4 ml/kg/min. A comparison of pre- and post-FC CPET data was performed using 42 patients (56%) that underwent CPET after FC. Improvement in EC occurred in 18 of 42 patients (43%). Baseline peak VO2 > 14 ml/kg/min was associated with improved EC (hazard ratio [HR] 1.85; P = .02). Improvement in New York Heart Association (NYHA) class occurred in 12 (67%) patients with improved EC vs 2 (8%) without improved EC. Improvement in NYHA class was more likely to occur in patients with improved EC compared to those without improvement EC (odds ratio 4.11, P = .01). There were 10 (13%) perioperative deaths, and baseline peak VO2 ≤ 14 ml/kg/min was predictive of perioperative mortality (HR 3.74; P < .001). Conclusions: Baseline peak VO2 was predictive of perioperative survival, and improvement in EC. Performance on CPET in failing Fontan patients might be a useful clinical parameter in determining appropriate timing of FC.